2021
DOI: 10.1021/acsami.1c08087
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Ion-Conducting Composite Membrane with Buckling-Induced Anisotropic Through-Plane Conductivity

Abstract: Fuel cell (FC) is an attractive green alternative for today's fuel combustion systems. In common FCs, a polymer electrolyte membrane selectively conducts protons but blocks the passage of electrons and fuel. Nafion, the current benchmark membrane material, has a superior conductivity owing to unique morphology comprising randomly oriented elongated ionic nanochannels within its Teflon-like matrix. Channel orientation enhances Nafion conductivity, yet there has been no facile method to induce a stable alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Nafion PEMs have high proton conductivity owing to the well-connected ionic pathways formed by their unique perfluorinated chemical structure . Actually, the existence of anisotropy between the in-plane and through-plane proton conductivity has been reported in Nafion membranes. The in-plane proton conductivity of Nafion PEMs was measured to be in the range of 80–120 mS·cm –1 with a four-probe electrode and the through-plane proton conductivity of Nafion PEMs was determined to be in the range of 20–50 mS·cm –1 by a two-probe electrode. , The measurement results of the proton conductivity of Nafion PEMs by the four-probe electrode method are usually higher than those by the two-probe electrodes. It has been reported that the PEM with high through-plane proton conductivity is profitable in preparing high-performance fuel cells. However, Nafion PEMs still suffer from certain limitations including a complex synthetic process, high production cost, and high fuel permeability. , Nonperfluorinated hydrocarbon-based materials with rigid polymer chains, such as sulfonated poly(aryl ether ketone), , sulfonated poly(ether ether ketone), sulfonated poly(arylene ether sulfone), sulfonated polybenzimidazole, sulfonated polystyrene, etc., have been reported to be potentially applied to proton exchange membranes. In particular, polystyrene-based triblock copolymer thermoplastic elastomers containing middle soft rubbery segments, such as polystyrene- b -poly(ethylene- co -butylene)- b -polystyrene (SEBS) and polystyrene- b -polyisobutylene- b -polystyrene (SIBS) block copolymers, e...…”
Section: Introductionmentioning
confidence: 99%
“…Nafion PEMs have high proton conductivity owing to the well-connected ionic pathways formed by their unique perfluorinated chemical structure . Actually, the existence of anisotropy between the in-plane and through-plane proton conductivity has been reported in Nafion membranes. The in-plane proton conductivity of Nafion PEMs was measured to be in the range of 80–120 mS·cm –1 with a four-probe electrode and the through-plane proton conductivity of Nafion PEMs was determined to be in the range of 20–50 mS·cm –1 by a two-probe electrode. , The measurement results of the proton conductivity of Nafion PEMs by the four-probe electrode method are usually higher than those by the two-probe electrodes. It has been reported that the PEM with high through-plane proton conductivity is profitable in preparing high-performance fuel cells. However, Nafion PEMs still suffer from certain limitations including a complex synthetic process, high production cost, and high fuel permeability. , Nonperfluorinated hydrocarbon-based materials with rigid polymer chains, such as sulfonated poly(aryl ether ketone), , sulfonated poly(ether ether ketone), sulfonated poly(arylene ether sulfone), sulfonated polybenzimidazole, sulfonated polystyrene, etc., have been reported to be potentially applied to proton exchange membranes. In particular, polystyrene-based triblock copolymer thermoplastic elastomers containing middle soft rubbery segments, such as polystyrene- b -poly(ethylene- co -butylene)- b -polystyrene (SEBS) and polystyrene- b -polyisobutylene- b -polystyrene (SIBS) block copolymers, e...…”
Section: Introductionmentioning
confidence: 99%